Dissemination of food safety and determination of expiration of home industry products in Batuah Village, Kutai Kartananegara - Noor, M. Fauzan; Sukmana, Eman; Uhai, Sabalius; Sudarmayasa, I Wayan (Community Empowerment, 2021)
The purpose of the community service is to provide knowledge to the women villagers, so that they can set the expiration date for their product and to facilitate the PIRT (Home Industry Production) number registration. The method is carried out by inviting guest speakers from the Kutai Kartanegara District Health Office regarding the certification of home industry production. The results of the community service revealed that the partners increased their abilities as indicated by the post test score is over 60.